Comparative Study of Characteristicsof Sediment and Water Qualityin Aquaculture Farming Systems Area with Coastal Area Adjacent to Industrial Activities - Putro, Sapto Purnomo; Febria, Ibni Jeudi; Muhammad, Fuad (JURNAL SAINS DAN MATEMATIKA, 2014)
Disturbance of water environment due to organic enrichment caused by farming activities may result in the reduction of water quality and sediments. This study was conducted to determine the condition of the water and sediments in the area of aquaculture in ponds system compared to the adjacent coastal area of industrial activities. Water qualities observed were the temperature, DO, salinity, conductivity, turbidity and pH. Sediment characteristics measured were sediment grain size and organic matter content contained in the sediments. From the research, the temperature values obtained ranged 28.7-32.9Â°C, DO 3.63 to 6.4 mg/l, pH 4.31 to 6.27, salinity 4.6 to 33 â€°, conductivity 8.5- 50.2 ms/cm, turbidity 73-535 NTU. The substrate grain analysis showed at the fish farm area in pond systems was dominated by silt 71.70% and clay 16.71%. In the coastal area adjacent to the industrial activities, 93.38% substrate was dominated by sand. Analysis of organic matter content in the pond systems exhibited the highest ranged between 0.72% -1.16% for nitrogen and 3.20%-10.35% for carbon. The differences in the composition of the substrate and the organic material can be caused by hydrographic conditions, especially strong/weak water currents, the accumulation of litter originating from the decomposition of leaves of mangrove, enrichment of nutrients during the decomposition of litter and aquaculture activities and industries.